2020
DOI: 10.1039/d0fo00807a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacement of antibiotics with thyme and celery seed mixture on the feed intake and digestion, ruminal fermentation, blood chemistry, and milk lactation of lactating Barki ewes

Abstract: The study investigated the effect of in-feed administration of dried thyme leaf and celery seed mixture (at 1 : 1 w/w) compared with salinomycin ionophore on milk production and milk nutritive value of Barki ewes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
2
11
0
1
Order By: Relevance
“…The improved digestion confirmed that the dose of Marjoram or Basil oils were lower than that dose which destroys the activities of ruminal microorganisms (Walsh et al, 2003). These results were in agreements with Khattab et al (2020b) who found that the dry matter digestibility increased by thyme supplementation to ewes' diets (20g/h/d).…”
Section: Gas Productionsupporting
confidence: 88%
“…The improved digestion confirmed that the dose of Marjoram or Basil oils were lower than that dose which destroys the activities of ruminal microorganisms (Walsh et al, 2003). These results were in agreements with Khattab et al (2020b) who found that the dry matter digestibility increased by thyme supplementation to ewes' diets (20g/h/d).…”
Section: Gas Productionsupporting
confidence: 88%
“…No significant difference in dry matter (P = 0.2809), NDF (P = 0.9874) and ADF (P = 0.2089) degradability among groups. These results indicated that the concentrations of active components in marjoram or basil leaves insufficient to effect on the microbial activity in the rumen, and sequentially nutrients digestion [10,11,12,43].These results were agreement with Selim et al [15]who found no (p>0.05) variances in cellwall contents (NDF and ADF) degradability by marjoram or basil oils supplementations in-vitro. Also, Khattab et al [12] found the similar results when they used thyme and celery in in-vitro study.…”
Section: Nutrients Degradabilitysupporting
confidence: 83%
“…Key words: feed utilization, fennel, ginger, ionophores, milk fatty acids, milk production For many years, herbal and medicinal plants feed additives have been used to stimulate appetite and digestion in ruminants and keep animal's health (Cedillo et al, 2015;Salem et al, 2017). Moreover, phytogenic compounds have been used in lieu of performance promoters (i.e., antibiotic ionophores) (Matloup et al, 2017;Khattab et al, 2020). Phytogenic additives include, for example, essential oils, herbs or seeds (Abd El Tawab et al, 2020).…”
mentioning
confidence: 99%